Screening of brazilian plants for the presence of peroxides (Revista Brasileira de Ciências Farmacêuticas, 2002)
Chloroform or dichloromethane extracts of 357 southern Brazilian plant species were tested for the presence of peroxides by thinlayer chromatography, using the spray reagent from Huber & Fröhlke. From the species tested, 71 (20%) showed positive results and most of them (56%) are Asteraceae species. The species tested were mainly from Asteraceae, but 55 more families were screened, in a total of 77 genera surveyed.